USM TO ORGANISE THE INTERNATIONAL CONFERENCE ON LOCAL KNOWLEDGE (ICLK) 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM PENANG, 23 March 2016 – The International Conference on Local Knowledge (ICLK) 2016 Secretariat extends an invitation to experts, scholars and practitioners in the field to attend the conference from 27 – 28 July 2016 in Penang, Malaysia with the theme ‘Universal Heritage’.